Tinjauan Komprehensif Mengenai Harga Transfer:Konsep Manajerial, Metode Biaya, Dan Implikasi Perpajakan - Arya Septa Christian Hiu Wibawa,; Astatari,; Devino Harun Alamsyah Putra,; Nazhwa Erisindya,; Haliza Laily Ningrum,; Jovant Arryzona Putra Pramudya, (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
Transfer Pricing (TP) is a topic with a dual role: as an internal managerial tool and as a crucial issue in international taxation. Broadly defined, TP is the price at which goods or services are transferred between units or responsibility centers within an organization. Its primary managerial objectives are to distribute profits between profit centers, provide relevant information to business units to achieve optimal balance, create goal congruence, and assist in measuring the economic performance of individual business units. Furthermore, TP serves as an integration mechanism between sales and purchasing divisions within a diversified company. In determining TP, cost-based methods such as Activity Based Costing (ABC) and Full Costing are reviewed as ways to achieve more accurate and fair calculations, both for large companies and Small and Medium Enterprises (SMEs). Regulatory requirements for TP practices in Indonesia must comply with the Arm's Length Principle. TP practices in multinational corporations (MNCs) are known to be associated with tax avoidance and profit shifting. The results of the study indicate that factors such as company size and tunneling incentives (foreign ownership) have a significant positive influence on transfer pricing policy, while the influence of tax avoidance and the number of independent commissioners has varied, and some are even insignificant. Companies generally disclose related party information in accordance with PSAK No. 7 of 2015.